Production and optimization of alkalostable lipase by alkalophilic Burkholderia cenocepacia ST8 - Lau, H. L.; Ariff, Arbakariya; Woo, Kwan Kit; Ling, Tau Chuan; Hii, Siew Ling (Academic Journals, 2011)
A superior lipase-producing bacterium was isolated from forest soil samples in Setapak, Malaysia and it was identified as Burkholderia cenocepacia with 16S rRNA sequencing technique. Multifactor experimental design based on ‘change-one-factor-at-a-time’ approach was employed to optimize the production of Bukholderia lipase with submerged fermentation technique. Effects of carbon and nitrogen sources, metal ions as well as initial pH of medium on lipase production were extensively investigated. Optimal lipase activity was achieved in medium using combination of sunflower oil and Tween 80 (1% v/v each) as carbon sources. Simple sugars such as glucose and fructose, however, did not promote the production of lipase. Peptone (from meat) at 0.33% (w/v) was the most suitable nitrogen source for lipase production by this Gram-negative bacterium. The presence of Ca2+ in the cultivation medium possessed significant effect on lipase production while Mg2+, Mn2+, Na+, Fe2+, Cu2+ and Co2+ exhibited inhibitory effect towards the enzyme production. Initial culture pH in the range of 5 to 11 were found suitable for lipase production, with the maximum level of lipase activity recorded in the medium with initial culture pH of 9.0.